A case study of a young patient with recurrent myocardial infarction - Liudmila, Kalatsei; Kokwewa, R. B. S. W. M. Pasan M.; Gawarammana, M. M. Shalini P. (International Journal of Research in Medical Sciences, 2025)
Although myocardial infarction (MI) mainly occurs in patients over 50 years of age, this pathology is registered annually in younger patients. The development of MI at a young age is associated with cardiovascular complications, the risk of anxiety and depressive disorders, socio-economic consequences due to disability and the inability to continue professional activity. The most common causes of MI in patients under 50 years of age include coronary thrombosis due to coronary artery atherosclerosis, non-atheromatous coronary artery disease; congenital and acquired thrombophilic conditions and conditions associated with hypercoagulability; MI associated with the use of psychoactive substances. This article describes a clinical case of MI in a 36-years-old patient, with 30% occlusion of the circumflex artery and 70% occlusion of the first branch of obtuse marginal artery and provides a detailed review of the investigations done. And also, it discusses practical issues related to the management of this category of patients. We have further depicted the prognosis of PCI by using the SPECT investigation before and after PCI.